Asuhan Keperawatan Perfusi Perifer Tidak Efektif dengan Intervensi Perawatan Kaki pada Pasien Diabetes Mellitus Tipe 2 di Ruang Aqsa 2 RSUDZA Banda Aceh - Husna Faidzi; Maimun Tharida; Nanda Desreza (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Type 2 Diabetes Mellitus (DM) is a chronic disease that can lead to impaired peripheral perfusion and increase the risk of complications in the lower extremities. Foot care is one of the essential nursing interventions to prevent these complications. This scientific paper aims to describe nursing care through foot care interventions in patients with type 2 DM experiencing ineffective peripheral perfusion in Aqsa 2 Ward, Zainal Abidin Regional General Hospital, Banda Aceh. The method used is a case study with a nursing process approach, including assessment, diagnosis, intervention, implementation, and evaluation. The assessment results showed that the patient experienced ineffective peripheral perfusion, characterized by tingling in the feet, pale skin, and decreased peripheral circulation. The interventions provided included foot care education, maintaining foot hygiene, routine foot inspection, and foot exercises. After the nursing interventions were implemented, there was a reduction in complaints in the lower extremities and an increase in the patient’s knowledge regarding the prevention of diabetes complications. The conclusion shows that foot care is effective in improving peripheral perfusion and preventing complications in patients with type 2 DM. Therefore, foot care should be performed routinely as part of self-care in diabetes patients.